Perceived Organizational Support as a Mediator of HRM Practices on Retention and Engagement in Indonesian Start-ups - Dana Budiman; Rakotoarisoa Maminiaina Heritiana Sedera; Supriandi Supriandi; Agung Maulana (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Indonesian start-up face high turnover and engagement challenges, making effective human resource management crucial for success. This study explores how digital human resource management practices, psychological empowerment, job flexibility, and career development influence employee retention and work engagement, with perceived organizational support as a mediator. Using a quantitative approach, we surveyed 215 employees from technology and e-commerce start-up in Jakarta, Bandung, and Yogyakarta, employing Structural Equation Modeling-Partial Least Squares for analysis. The findings show that digital human resource management practices, psychological empowerment, job flexibility, and career development positively impact perceived organizational support, which in turn enhances retention and engagement, with a stronger effect on engagement. These results, grounded in Social Exchange Theory, highlight the importance of fostering a supportive workplace to boost employee commitment. However, the study’s focus on urban tech start-up limits its applicability to other sectors. Future research could explore diverse industries or longitudinal designs. This study offers startup leaders insights into building strategies that strengthen employee loyalty and enthusiasm in Indonesia’s dynamic startup ecosystem.